2021
DOI: 10.1002/dc.24885
|View full text |Cite
|
Sign up to set email alerts
|

BRD3‐NUTM1‐expressing NUT carcinoma of lung on endobronchial ultrasound‐guided transbronchial needle aspiration cytology, a diagnostic pitfall

Abstract: Background Nuclear protein in testis (NUT) carcinoma (NC) is an aggressive type of poorly differentiated carcinoma with a variable degree of squamous differentiation. NC is defined by the presence of BRD‐NUT fusion oncogenes, the most common fusion form being the BRD4‐NUTM1 gene. Variant rearrangements involving the BRD3 and NSD3 genes. Variant rearrangements involving the BRD3 and NSD3 genes occur in approximately one‐third of the cases. Aims This is the first case regarding the study of cytological features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The case report from Zhu et al discussed a subcarinal mass showing nests and pseudopapillary arrays of undifferentiated, epithelioid cells with similar cytologic findings as ours, 5 whereas a case from French et al described a well‐differentiated squamous cell carcinoma and another revealing a poorly differentiated carcinoma 7 . Aryal et al reported on the transbronchial cytologic findings of rare, atypical squamoid cells with nucleoli, high NC ratios, rare keratinization and keratin pearls 9 . Dickson et al reported on a left thigh BRD3‐NUT NC that revealed predominantly epithelioid cells but with focal regions of syncytial pattern and another region with epithelioid‐rhabdoid morphology 8 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The case report from Zhu et al discussed a subcarinal mass showing nests and pseudopapillary arrays of undifferentiated, epithelioid cells with similar cytologic findings as ours, 5 whereas a case from French et al described a well‐differentiated squamous cell carcinoma and another revealing a poorly differentiated carcinoma 7 . Aryal et al reported on the transbronchial cytologic findings of rare, atypical squamoid cells with nucleoli, high NC ratios, rare keratinization and keratin pearls 9 . Dickson et al reported on a left thigh BRD3‐NUT NC that revealed predominantly epithelioid cells but with focal regions of syncytial pattern and another region with epithelioid‐rhabdoid morphology 8 .…”
Section: Discussionmentioning
confidence: 61%
“…7 Aryal et al reported on the transbronchial cytologic findings of rare, atypical squamoid cells with nucleoli, high NC ratios, rare keratinization and keratin pearls. 9 Dickson et al reported on a left thigh BRD3-NUT NC that revealed predominantly epithelioid cells but with focal regions of syncytial pattern and another region with epithelioidrhabdoid morphology. 8 Our case did not show evidence of squamous differentiation, rhabdoid or syncytial patterns.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated 55 patients (36 men and 19 women) among the 35 articles [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] with a mean age of 41.4 years (range, 6–82). The male to female ratio was approximately 1.89 to 1.…”
Section: Resultsmentioning
confidence: 99%
“…2,4,5 Moreover, BRD3 (15%) and NSD3 (6%) are additional fusion partners identified in NC. 3,[6][7][8][9] NC is highly lethal, with a median overall survival of 6.7 months. 2 While NC can occur at any age, it mainly affects children and young adults, with a median age at diagnosis of 23.6 years.…”
Section: Introductionmentioning
confidence: 99%